Concerned friends of intimate partner violence survivors: results from the myPlan randomized controlled trial on college campuses - Tina L. Bloom; Nancy Perrin; Megan Lindsay Brown; Jacquelyn Campbell; Amber Clough; Karen Trister Grace; Kathryn Laughon; Jill Messing; Karen B. Eden; Rachael Turner; Nancy Glass (BMC, 2023)
Abstract Background Nearly half of intimate partner violence (IPV) survivors experience their first abusive relationship at college age (18-24 years). Most often they disclose the violence to friends. Existing college campus "bystander" interventions training peers to safely intervene have been effective in sexual assault prevention; similar interventions have rarely been tested for IPV. Therefore, we evaluated the effectiveness of an interactive, personalized safety decision and planning tool, myPlan app, on decisional conflict, decisional preparedness, confidence in intervening, supportive safety behaviors, and IPV attitudes with concerned friends of abused college women. Methods We recruited college students (age 18-24, N = 293) of any gender who had a female-identified friend who had recently experienced IPV ("concerned friends") from 41 Oregon and Maryland colleges/universities. Participants were randomized to myPlan (n = 147) or control (usual web-based resources; n = 146). Outcomes included decisional conflict, decisional preparedness, confidence to intervene, safety/support behaviors, and IPV attitudes. Results At baseline, concerned friends described the abused person as a close/best friend (79.1%); 93.7% had tried at least one strategy to help. Most (89.2%) reported concerns their friend would be seriously hurt by the abuser; 22.7% reported extreme concern. Intervention participants had greater improvements in decisional conflict (specifically, understanding of their own values around the decision to intervene and help a friend) and decisional preparedness immediately after their first use of myPlan, and a significantly greater increase in confidence to talk with someone about their own relationship concerns at 12 months. At 12-month follow-up, both intervention and control groups reported increased confidence to intervene, and did not differ significantly in terms of percentage of safety/support strategies used, whether strategies were helpful, or IPV attitudes. Conclusions A technology-based intervention, myPlan, was effective in reducing one aspect of decisional conflict (improving clarity of values to intervene) and increasing decisional preparedness to support a friend in an unsafe relationship. Information on IPV and related safety strategies delivered through the myPlan app or usual web-based resources both increased confidence to intervene with a friend. College students in the myPlan group were more likely to talk with someone about concerns about their own relationship, demonstrating potential for IPV prevention or early intervention. Trial registration Clinicaltrials.gov ID: NCT02236663, registration date 10/09/2014.